PENGARUH PENGENDALIAN INTERNAL DAN KONEKSI POLITIK TERHADAP PENGHINDARAN PAJAK (STUDI PADA PERUSAHAAN BEI SEKTOR PROPERTY AND REAL ESTATE PERIODE 2020-2021) - Lailani Fitria; Dwi Waliyatul Azizah; Arief Setiawan; Monica Feronica Bormasa; Widyatmoko Widyatmoko (ITB AAS Indonesia Surakarta, 2024)
Tax avoidance is part of the methods used by companies to reduce tax cost. Companies consider tax as burden, which can result in reduced company profit, so many companies carry out tax avoidance activities to minimize the tax burden so that company profits are large. There are factors that influence tax advoidance, including GCG, institutional/political ownership, internal control, family ownership and evironmental uncertainty. This reseacrh method uses quantitative research with descriptive analysis. The population was 10 companies with the research year 2019-2021 and the reseacrh sample obtained was 30 financial reports. Previous research discussing tax advoidance focused on company size and GCG, and many case studies were conducted on manufacturing companies. Therefore, this research tries to look at tax advoidance in property and real estate companies with internal control variables and political connections. This result of this research show that internal control variables and political connection have a negative effect on tax advoidance.